ChemInform Abstract: Nanometals for Solar‐to‐Chemical Energy Conversion: From Semiconductor‐Based Photocatalysis to Plasmon‐Mediated Photocatalysis and Photo‐Thermocatalysis. Issue 44 (13th October 2016) - Meng, Xianguang; Liu, Lequan; Ouyang, Shuxin; Xu, Hua; Wang, Defa; Zhao, Naiqin; Ye, Jinhua
Abstract: Review: 197 refs.